Utility indices for brown brocket deer (mazama gouazoubira) - Mucciolo, Leonardo; Acosta, Alejandro (Revista Chilena de Antropología, 2015)
We present results of a butchery experiment of a brown brocket deer (Mazama gouazoubira) individual, which was employed to calculate several utility indexes for this species: MUI (Meat Utility Index), GUI (General Utility Index), y FUI (Food Utility Index). Results are compared with those of larger cervids like caribou, huemul and white-tailed deer, indicating a strong and positive correlation.